Implications for driving based on the risk of seizures after ischaemic stroke - Schubert, Kai Michael; Bicciato, Giulio; Sinka, Lucia; Abraira, Laura; Santamarina, Estevo; Álvarez-Sabín, José; Ferreira-Atuesta, Carolina; Katan, Mira; Scherrer, Natalie; Terziev, Robert; Döhler, Nico; Erdélyi-Canavese, Barbara; et al. (Journal of neurology, neurosurgery, and psychiatry, 2024)
Background In addition to other stroke-related deficits, the risk of seizures may impact driving ability after stroke. - Methods We analysed data from a multicentre international cohort, including 4452 adults with acute ischaemic stroke and no prior seizures. We calculated the Chance of Occurrence of Seizure in the next Year (COSY) according to the SeLECT2.0 prognostic model. We considered COSY<20% safe for private and <2% for professional driving, aligning with commonly used cut-offs. - Results Seizure risks in the next year were mainly influenced by the baseline risk-stratified according to the SeLECT2.0 score and, to a lesser extent, by the poststroke seizure-free interval (SFI). Those without acute symptomatic seizures (SeLECT2.0 0-6 points) had low COSY (0.7%-11%) immediately after stroke, not requiring an SFI. In stroke survivors with acute symptomatic seizures (SeLECT2.0 3-13 points), COSY after a 3-month SFI ranged from 2% to 92%, showing substantial interindividual variability. Stroke survivors with acute symptomatic status epilepticus (SeLECT2.0 7-13 points) had the highest risk (14%-92%). - Conclusions Personalised prognostic models, such as SeLECT2.0, may offer better guidance for poststroke driving decisions than generic SFIs. Our findings provide practical tools, including a smartphone-based or web-based application, to assess seizure risks and determine appropriate SFIs for safe driving.
Zu diesem Artikel gibt es Supplementary Material
Online veröffentlicht: 15. Mai, 2024
Gesehen am 23.10.2024